ANALISA PEMBELIAN KOPI DI DIALOGKOPI SUKOHARJO - Candra Nugroho; Bambang Mursito; Sudarwati Sudarwati (JURNAL ILMIAH EDUNOMIKA, 2019)
This study aims to determine the effect of partial and simultaneous coffee purchases at the Dialogue in Sukoharjo. This type of research is quantitative research. The population in this study were 100 people in Dialogkopi Sukoharjo, while the sample used was 25. Then the data were analyzed using SPSS version 22, with quantitative analysis which included validity and reliability tests, classic assumption tests, multiple linear regression analysis, hypothesis testing with F test and t test and coefficient of determination. The F test results indicate that product quality, price and location simultaneously and significantly influence purchasing decisions at Dialogkopi Sukoharjo. The results of the t test show that product quality has a positive and significant effect on purchasing decisions at Dialogkopi Sukoharjo , the value of having a positive and significant influence on purchasing decisions at Dialogkopi Sukoharjo and location has a positive and significant effect on purchasing decisions at Dialogkopi Sukoharjo. The coefficient of determination shows that the variables of product quality, price and location have an influence of 72.6% on the purchasing decision variable at Dialogkopi Sukoharjo Keywords: Product quality, price, location, purchase decision